The near-surface layer of the ocean structure, dynamics and applications - Soloviev, Alexander. (Atmospheric and oceanographic sciences library)
The Near-Surface Layer of the Ocean provides a comprehensive account of the structure and dynamics of this important component of the ocean. The book develops the relevant physics and thermodynamics in depth. Detailed treatment is given to the surface microlayer, upper-ocean turbulence, fine thermohaline structure, coherent structures, high wind-speed regime, and to practical applications. Results of major air-sea interaction experiments (including those obtained with the participation of the authors) are used in the analysis. Sea surface microlayer -- Near-surface turbulence -- Fine structure and microstructure -- Spatially-varying and coherent structures -- high wind speed regime -- applications.